regium@Lepidi 2200 - Forte, Maurizio; Danelon, Nevio (Archeomatica, 2019)
regium@Lepidi 2200 is an international project designed with the scope to study and virtually reconstruct the Roman city of Regium Lepidi (Reggio Emilia). The final aim is the creation of a new virtual museum and IT room designed within the archaeological museum of Reggio Emilia.